Art Therapy in the Digital World: An Integrative Review of Current Practice and Future Directions - Zubala, Ania; Kennell, Nicola; Hackett, Simon (Frontiers in Psychology, 2021)
Background Psychotherapy interventions increasingly utilise digital technologies to improve access to therapy and its acceptability. Opportunities that digital technology potentially creates for art therapy reach beyond increased access to include new possibilities of adaptation and extension of therapy tool box. Given growing interest in practice and research in this area, it is important to investigate how art therapists engage with digital technology or how (and whether) practice might be safely adapted to include new potential modes of delivery and new arts media. Methods An integrative review of peer-reviewed literature on the use of digital technology in art therapy was conducted. The methodology used is particularly well suited for early stage exploratory inquiries, allowing for close examination of papers from a variety of methodological paradigms. Both quantitative and qualitative research was synthesised. Only studies that presented empirical outcomes were included in the formal analysis. Findings Over 400 records were screened and 13 papers were included in the synthesis, pertaining to both the use of digital technology for remote delivery and as a medium for art making. Recurring themes are discussed, including potential benefits and risks of incorporating digital technology in sessions with clients, concerns relating to ethics, resistance towards digital arts media, technological limitations and implications for therapeutic relationship and therapy process. Propositions for best practice and technological innovations that could make some of the challenges redundant are also reviewed. Future directions in research are indicated and cautious openness is recommended in both research and practice. Conclusions The review documents growing research illustrating increased use of digital technology by art therapists for both online delivery and digital art making. Potentially immense opportunities that technology brings for art therapy should be considered alongside limitations and challenges of clinical, pragmatic and ethical nature. The review aims to invite conversations and further research to explore ways in which technology could increase relevance and reach of art therapy without compromising clients’ safety and key principles of the profession.